Low-energy Ar+ ion-beam-induced chemical vapor deposition of silicon dioxide films using tetraethyl orthosilicate. Issue 4 (April 2023) - Yoshimura, Satoru; Sugimoto, Satoshi; Takeuchi, Takae; Kiuchi, Masato
Abstract: This study was conducted to determine whether the simultaneous injections of Ar + ions and tetraethyl orthosilicate (TEOS) to a substrate are able to fabricate a film on the substrate. The Ar + ion energy was 100 eV. After the injections, we found a film deposited on the substrate. Following the analyses of the film with X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy, it was found that the deposited film was silicon dioxide (SiO2 ). We conclude that the low-energy Ar + ion-beam-induced deposition method using TEOS is useful for the growth of SiO2 films. Highlights: A film deposition method by ion-beam-induced chemical vapor deposition (IBICVD). We selected Ar + ions as ion beams for IBICVD. We used tetraethyl orthosilicate (TEOS) as a source material for IBICVD. SiO2 film was formed when Ar + ions were irradiated in conjunction with TEOS.